Mooseltoe - Palatini, Margie; Cole, Henry, 1955- (New York : Hyperion Books for Children, 2000)
Moose thinks he has all his Christmas preparations taken care of, but at the last minute he must come up with a substitute for the Christmas tree.
Booklist.
2.8
K-3
Keywords: Christmas -- Juvenile fiction; Christmas trees -- Juvenile fiction; Moose -- Juvenile fiction; Mustaches -- Juvenile fiction; Christmas -- Fiction; Christmas trees -- Fiction; Moose -- Fiction; Mustaches -- Fiction; Christmas -- Fiction; Christmas trees -- Fiction; Moose -- Fiction; Mustaches -- Fiction; Christmas -- Fiction; Christmas trees -- Fiction; Moose -- Fiction